The Role of Emotional Intelligence in Improving Early Childhood Social and Academic Skills - Arinda, Fita; Oo, Zaw Min; Myint, Aung; Anggreni, Made Ayu (World Psychology, 2025)
Emotional intelligence (EI) plays a critical role in early childhood development, influencing social and academic skills. As young children begin to navigate complex social interactions and engage in learning activities, the ability to recognize, understand, and regulate emotions becomes fundamental to their success in school and relationships. Despite its importance, the role of EI in shaping early childhood social and academic outcomes remains underexplored. This study aims to examine the impact of emotional intelligence on the development of social and academic skills in early childhood. A mixed-methods approach was employed, involving a sample of 150 preschool children and their teachers. The study utilized the Emotional Quotient Inventory (EQ-i) for children and teacher reports on social and academic skills. The results demonstrated that higher emotional intelligence scores were significantly associated with better social interactions, peer relationships, and academic performance, particularly in areas of problem-solving and self-regulation. The findings suggest that fostering emotional intelligence in early childhood education programs can enhance both social and academic competencies. The study concludes that EI is a key factor in supporting children’s overall development, providing a foundation for improved social interactions and academic achievement in later years.